The Emissions, Energy Consumption, and Growth Nexus: Evidence From the Commonwealth of Independent States - Apergis, Nicholas; Payne, J. (Elsevier Science Ltd., 2010)
This study examines the causal relationship between carbon dioxide emissions, energy consumption, and real output within a panel vector error correction model for eleven countries of the Commonwealth of Independent States over the period 1992–2004. In the long-run, energy consumption has a positive and statistically significant impact on carbon dioxide emissions while real output follows an inverted U-shape pattern associated with the Environmental Kuznets Curve (EKC) hypothesis. The short-run dynamics indicate unidirectional causality from energy consumption and real output, respectively, to carbon dioxide emissions along with bidirectional causality between energy consumption and real output. In the long-run there appears to be bidirectional causality between energy consumption and carbon dioxide emissions.